HUMAN DIGNITY: A STIMULUS FOR THE (SOCIAL) GOSPEL (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Firstly, in this article we analyze and reflect upon a religious and social reform movement, known as the Social Gospel. This movement took place within the liberal Protestant tradition, mainly in the United Stated of America, at the beginning of the twentieth century. The aim of the Social Gospel was to apply the biblical principles to the industrialized American society in order to produce a “social salvation” at large. There was a strong belief that education, charity and justice can transform the nation and release it from poverty and other social issues. We focus on this movement by looking at the teachings and thought of some of its leaders, such as Walter Rauschenbuch, Washington Gladden and others. Secondly, we argue that human dignity was an important stimulus for the development of the Social Gospel. We try to prove this by showing the connection between the concept of human dignity and the tenets of the movement itself and by indicating some relevant writings and quotations from the Social Gospel camp. However, building on the limitations of the Social Gospel, which are noticeable in some of the critiques of the movement, we suggest that human dignity is not a stimulus merely for the Social Gospel but for the Gospel itself. The main point which is developed is that human dignity, instead of being reduced to the physical world, should be considered in its eternal existence.